2008
DOI: 10.1109/tse.2008.35
|View full text |Cite
|
Sign up to set email alerts
|

Benchmarking Classification Models for Software Defect Prediction: A Proposed Framework and Novel Findings

Abstract: Abstract-Software defect prediction strives to improve software quality and testing efficiency by constructing predictive classification models from code attributes to enable a timely identification of fault-prone modules. Several classification models have been evaluated for this task. However, due to inconsistent findings regarding the superiority of one classifier over another and the usefulness of metric-based classification in general, more research is needed to improve convergence across studies and furt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
663
2
14

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 1,045 publications
(716 citation statements)
references
References 61 publications
16
663
2
14
Order By: Relevance
“…Information has been also used by earlier studies ( [16] NNP [17] [18] NNS NASA classifier. SVM MDP repository and an.…”
Section: Discussionmentioning
confidence: 99%
“…Information has been also used by earlier studies ( [16] NNP [17] [18] NNS NASA classifier. SVM MDP repository and an.…”
Section: Discussionmentioning
confidence: 99%
“…3. In the domain of software defect prediction, often the data sets under study represents less than 1 percent of the data point in total [1], [10] and [11]. Referencing [5] presented an example of using the most imbalanced of the NASA Metric Data Program; PC2.…”
Section: A Analysis Of Precision Measurementioning
confidence: 99%
“…In software defect prediction studies, it is also empirically shown that the performance of the Naïve Bayes is amongst the top algorithms [17]. As shown in Table 6, datasets are imbalanced.…”
Section: Construction Of the Prediction Modelmentioning
confidence: 99%
“…As a result, both increasing the efficiency of the software testing phase and delivering the software product to the market on time become possible. Reported results in software defect prediction literature suggest that further progress in defect prediction performance can be achieved by increasing the content of input data that defect predictors learn rather than using different algorithms or increasing the size of input data [17], [15], [16]. We can group some significant work in the literature in terms of their focus: algorithm driven approaches; data size driven approaches; and data content driven approaches.…”
mentioning
confidence: 99%